PJBL-Based Digital Modules Integrated With Chemo-Entrepreneurship In Hydrocarbon Learning In Indonesia: A Systematic Literature Review - Triana Putri Sitorus; Maria Erna; Wulandari Wulandari (Lembaga Riset dan Inovasi Almatani, 2026)
The transformation of 21st-century education requires chemistry learning to move beyond conceptual mastery and foster students' critical thinking, creativity, digital literacy, and entrepreneurial skills. One promising approach to addressing these demands is the integration of Project-Based Learning (PjBL), chemo-entrepreneurship (CEP), and digital modules in chemistry education. This study aims to analyze research trends related to the development of PjBL-based digital modules integrated with chemo-entrepreneurship in chemistry learning, particularly on hydrocarbon topics, during the period 2015–2025. The study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Data were collected from Scopus, ScienceDirect, SpringerLink, ERIC, Google Scholar, Garuda, and SINTA databases. The selection process resulted in 29 articles that met the inclusion criteria. The findings indicate that existing studies are predominantly focused on the development of e-modules, electronic worksheets (e-LKPD), and the implementation of PjBL to enhance critical thinking skills, creativity, science process skills, and entrepreneurial interest. However, studies that simultaneously integrate digital modules, PjBL, and chemo-entrepreneurship within hydrocarbon learning remain limited. Therefore, the development of PjBL-based digital modules integrated with chemo-entrepreneurship for hydrocarbon topics offers significant potential as an innovative learning strategy aligned with the demands of 21st-century education.